Shank3 Mice Carrying the Human Q321R Mutation Display Enhanced Self-Grooming, Abnormal Electroencephalogram Patterns, and Suppressed Neuronal Excitability and Seizure Susceptibility - Yoo, Ye-Eun; Yoo, Taesun; Lee, Seungjoon; Lee, Jiseok; Kim, Doyoun; Han, Hye-Min; Bae, Yong-Chul; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2019)
Shank3, a postsynaptic scaffolding protein involved in regulating excitatory synapse assembly and function, has been implicated in several brain disorders, including autism spectrum disorders (ASD), Phelan-McDermid syndrome, schizophrenia, intellectual disability, and mania. Here we generated and characterized a Shank3 knock-in mouse line carrying the Q321R mutation (Shank3Q321R mice) identified in a human individual with ASD that affects the ankyrin repeat region (ARR) domain of the Shank3 protein. Homozygous Shank3Q321R/Q321R mice show a selective decrease in the level of Shank3a, an ARR-containing protein variant, but not other variants. CA1 pyramidal neurons in the Shank3Q321R/Q321R hippocampus show decreased neuronal excitability but normal excitatory and inhibitory synaptic transmission. Behaviorally, Shank3Q321R/Q321R mice show moderately enhanced self-grooming and anxiolytic-like behavior, but normal locomotion, social interaction, and object recognition and contextual fear memory. In addition, these mice show abnormal electroencephalogram (EEG) patterns and decreased susceptibility to induced seizures. These results indicate that the Q321R mutation alters Shank3 protein stability, neuronal excitability, repetitive and anxiety-like behavior, EEG patterns, and seizure susceptibility in mice.